Biofilm Properties and Their Association to Antibiotic Resistance of Staphylococcus aureus from Animal Isolates - Aziz, Fatkhanuddin; Fitriana, Fauziah; Setyorini, Dian Ritma; Prihanani, Nur Ika; Andityas, Morsid (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Staphylococcus aureus (S. aureus) is a Gram positive bacterium that has many virulence factor including the ability to produce biofilm. Biofilm formation is one of the important ability in the persistance and resistant to antibiotic treatment. This study aimed to determine the phenotypic and genotypic characteristics of S. aureus isolates from animal origin in their capacity to produce biofilm in vitro. Eight S. aureus isolates collection from goat mastitis and raw chicken meat origin were phenotypically evaluated the ability to produce biofilm in 96 well culture plate, while genotypic were determinated by detecting the icaA, icaC and icaD genes. We employed  minimum of inhibitory concentration (MIC) data from previous research to clarify their correlation to biofilm production in respected isolates. The results showed that 75% (6/8) of S. aureus isolates had ability to produced biofilm, whereas 50% (4/8) showed the elevation of biofilm production after glucose was added. PCR determination showed that majority isolates were positive for icaA, icaC and icaD genes, while one of the isolates was negative for the icaA. The statistical analysis tests indicated no correlation between the optical density of biofilm production and MIC of antibiotics. Further research is needed to clarify the association of biofilm and antibiotic resistance.